Kolmogorov widths of the anisotropic Besov classes of periodic functions of many variables - Myronyuk, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We establish exact-order estimates for the Kolmogorov widths of the anisotropic Besov classes of periodic functions of many variables in the spaces $L_q,\; 1 ≤ q ≤ ∞$.